Effects of pregnancy sickness on infant-weight and maternal weight-gain among Ghanaian women - Tayie, F.A.K.; Lartey, A.; Asibey-Berko, E. (Ecology of Food Nutrition, 2001)
This study sought to assess the relationship between nausea and vomiting during pregnancy and infant birth-weight and maternal weight-gain. A cohort of 502 pregnant women attending antenatal clinics in Accra participated in the study. A sub-sample of 128 pregnant women participated in a longitudinal study that involved assessment of maternal weight-gain during pregnancy. The heights and weights of those in this subsample were measured in the first trimester followed by monthly measurements of their weights when they visited the antenatal clinics for care. During this time, information on nausea and vomiting were obtained by interview. The observed prevalence of nausea (loss of appetite with salivation and vomiting) among the pregnant women was 73.31%. Pregnant women who lost appetite with vomiting generally had infants of mean birth-weight significantly lower (p<0.05) than those who did not (2.87 kg±0.39 vs 3.21 kg±0.57, respectively). The mean pregnancy weight-gain of the mothers also followed a similar trend (10.16 kg±1.71 vs 11.05 kg±1.49). Subjects who vomited for more than three months had significantly lower pregnancy weight-gain and infant birth-weight (p<0.05) than those who never vomited or vomited for a lesser extent. There was a significant negative association between birth-weight and nausea r = -0.090 (p < 0.040, n = 502) and between birth-weight and months of vomiting, r = -0.073 (p < 0.030, n = 502). These findings show that nausea and vomiting during pregnancy are associated with a decrease in infant birth-weight and maternal weight-gain. These observations underscore the need for special care for pregnant women who experience nausea and vomiting.
Keywords: Birth-weight; Infant; Maternal; Nausea; Pregnancy; Vomiting; Weight-gain